Motorola India : on Razr thin ice - Walker, Russell, 1972- (London : Kellogg School of Management, 2019)
This case challenges students to consider how Motorola's share in the Indian market fall so dramatically while cell phone adoption in India skyrocketed and Motorola was launching one of its most successful products globally? The case is set in the mid-2000s, when Motorola had just rolled out the Razr phone and the firm was approaching its ten-year anniversary of its entry to the Indian market. Motorola's market share in India had fallen from as high as 31% in 1998 to less than 5% in 2006. This dramatic downturn came at a time of immense growth in the Indian cell phone market.
Originally Published InWalker, R. (2019). Motorola India: On Razr Thin Ice. 5-219-252. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Motorola, Inc. -- Case studies; Telecommunication -- India -- Case studies